Insekter för humankonsumtion NÄRINGSVÄRDET I INSEKTER TILLGÄNGLIGA PÅ DEN EUROPEISKA MARKNADEN - Benson, Julia; Johansson, Amanda; Vuong, Eddie; Havemeister, Fritjof; Nordberg, Johannes; Karlsson, Jakob (My University, 2019)
Insects for human consumption The nutritional quality of novel food entering European markets The rising global demand for meat puts a significant tension on the ecosystem and more sustainable alternative protein sources, which can substitute meat, are warranted. Insects have been suggested to serve as an alternative source to meat that could lead to diminished greenhouse gas emission produced by livestock. Before utilizing insects for food purpose, it is important to know their nutrient content. However, information about the composition of nutrients including macronutrients, vitamins and minerals are lacking for many insects. In the present study, the aim was to increase the knowledge regarding nutritional components in a selection of diverse edible insects. The analyzed components were phytic acid, vitamin E (α- and γ-tocopherol), amino acids, iron, zinc, copper and manganese. These nutrients were analyzed by different techniques including: High-Performance Liquid Chromatography (HPLC), Liquid Chromatography Mass Spectrometry (LCMS) and Atomic Absorption Spectroscopy (AAS). The insects analyzed were termite, buffalo worm, grasshopper, giant water bug, flying termite and yellow mealworm, in a total of eleven different samples. In all samples, the content of phytic acid was below the detection limit of the method (0.1 ppm). The content of α- and γ-tocopherol varied between the different insect species, with the highest content of α-tocopherol (0.556 mg/100g) found in grasshoppers whereas none were found in giant water bugs. In total 18 amino acids were quantified in all the samples and the content of amino acids varied within and between insects. Variations in copper concentration were found in the samples (0.5 - 2.7 mg/100g) as well as in iron concentration (1.9 - 19.6 mg/100g). The samples showed less variation in zinc concentration (3.5 - 4.6 mg/100g) apart from grasshoppers which had significantly higher content (7.6 mg/100 g). For manganese, the concentration found in different species of termites was significantly higher than expected (78 - 268 mg/100g). With exception of termites, based on the identified nutritional components suggest that the insects presented in this study can indeed be recommended as food or be served as a complement to a daily diet. Since the nutritional values varied significantly between several species the obtained data cannot support a general conclusion about nutritional contents in other insect species.
Keywords: Zoologi; Näringslära; Livsmedelsvetenskap; Livsvetenskaper; Zoology; Nutrition and Dietetics; Food Science; Life Science